Pemanfaatan Pekarangan Rumah Untuk Bertanam Sayur Kacang Panjang Kelompok Wanita Tani Serawai - Irawan, Veri; Sahputra, Royi; Agusmin, Wengki Abta; Sella, Sella; Sumartono, Eko (Jurnal INDONESIA RAYA (Pengabdian pada Masyarakat Bidang Sosial, Humaniora, Kesehatan, Ekonomi dan Umum), 2024)
Daily consumption of vegetables must be done because vegetables are very important for the human body. Therefore efforts are needed to get healthy vegetables at low prices. One effort that is very likely to be carried out by the community is to plant themselves in the yard of the house. The purpose of this service activity is to develop people's interest and motivation to be able to grow vegetables independently at home so that they can reduce spending and can achieve family food independence, especially in fulfilling vegetable nutrition. Home yards can be used to grow vegetables that can be consumed daily. Besides that, household waste can also be processed into fertilizers that can support vegetable growth. Thus, the community can save on expenditure because vegetables consumed are their own garden plants. From these activities, it can be suggested that citizens be more enthusiastic in utilizing their home yards to produce land, both for self-consumption or even marketable.